A novel polymer of Al2(SO4)3-poly(acrylamide-co-2-acrylamido-2-methyl-1-propanesulfonate) ionic hybrid prepared by dispersion polymerization (eXPRESS Polymer Letters)
A novel polymer Al2(SO4)3-poly(acrylamide-co-2-acrylamido-2-methyl-1-propanesulfonate) (Al2(SO4)3-P(AM/AMPS)) had been synthesized by dispersion polymerization in an aqueous solution of ammonium sulfate and aluminum sulfate, using poly(2-acrylamido-2-methyl-1-propanesulfonate) P(AMPS) as stabilizer, acrylamide (AM) and 2-acrylamido-2-methyl-1-propanesulfonate (AMPS) as monomers, poly(2-acrylamido-2-methyl-1-propanesulfonate) (PAMPS) as stabilizer and [2-(2-imidazdino-2-yl)propane]dihydrochloride (VA-044) as initiator. The average particle size of polymer dispersion ranged from 0.2 to 0.3 µm, the molecular weight was from 4.3•106 to 5.7•106 g•mol-1. The polymer was characterized by infrared (IR) spectroscopy, thermogravimetry (TGA) and transmission electron microscopy (TEM). The swelling property of the dispersion polymer was studied by particle size distribution. When the polymer dispersion was diluted with deionized water, particle sizes decreased several times. When the polymer dispersion was diluted with salt water, the particle size increased with increasing concentration of salt. The effects of Al2(SO4)3 and stabilizer on the particle size and the relative molecular weight of the polymer were investigated, respectively. The optimum conditions for the stable Al2(SO4)3-P(AM/AMPS) dispersion were that the concentration of Al2(SO4)3 was 1.12 wt%, the concentration of PAMPS stabilizer was 3 wt% and the concentration of initiator was 0.2 mol•l-1 and the monomers concentration was 14 wt%.